World context of religious change in the Caribbean. - DUKE, James T. (1995)
Describes changes in denominational affiliation in the Caribbean, and trends in the rate of conversion to religious denominations during the period 1900-1995. Explains the possible reasons for such changes, and discusses the Caribbean situation in the context of the broader world religious situation.